PENGARUH PENERAPAN MODEL PEMBELAJARAN CREATIVE PROBLEM SOLVING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII SMPN 3 KEC. PANGKALAN KOTO BARU - Maharani, Hijri (Departemen Matematika, 2024)
This experimental quantitative research analyses the effect of Creative Problem Solving model on the mathematical problem solving ability of students in class VIII SMPN 3 Kec. Pangkalan Koto Baru on students' mathematical problem solving ability. The design used was Posttest-Only Control. Experimental and control class students from SMPN 3 Kec. Pangkalan Koto Baru grade VIII in the 2023/2024 school year participated in this study. The sample selection was done by simple randomisation. Quiz and final test to collect data. Two-sample t-test for normality, homogeneity, and hypothesis testing were conducted. The final test results rejected H0 with a P-value of 0.006 and an actual level of 5%. H0 was rejected, therefore the experimental class learners answered the maths questions better than the control class learners. Thus, the Creative Problem Solving learning paradigm improves the mathematics problem-solving ability of grade VIII students at SMPN 3 Kec. Pangkalan Koto Baru.Keywords: Model CPS, Mathematical Problem Solving Skills, Direct Learning